Penerapan Strategi Marketing Jasa Pendidikan pada Masa Pandemi Covid-19 di SMK Al Muttaqin OKU Timur Sumatera Selatan - Moh. Adzkiyaunuha (Idaarotul Ulum, 2021)
The aim of this study was to describe and to analyze factors which the implementation of educational service marketing strategi. The type of research used is field research using a qualitative method. The data collection instrument was carried out by interview, observation dan documentation. The informants are participal, assistant principal of academic and student affairs, promotion team, educational consumer (society). Data sources are used in the form of primer and secondary data. Research result indicates that the implementation of educational service marketing strategy during covid-19 pandemic in SMK Al Muttaqin OKU Timur Sumatera Selatan which focuses on positioning activity (decide marketing position) indicate that this implementation has been well implemented. It can be seen from several indicators which are fulfilled in implementation of educational service marketing strategy on positioning activity that are educational institution provide marketing attribute or media, institution describes good prospect for alumnus and gives valid information related to aducational fee on educational marketing activity. Supporting factors of positioning activity are educational background of teachers and staff, sufficient facilities and infrastructure, strategic school location that is easy to be reached by educational consumer. While inhibiliting factors are price regulation or educational fee and process of educational product offers.